DJ-1 promotes osteosarcoma progression through activating CDK4/RB/E2F1 signaling pathway - Han, Zhitao; Wang, Lining; Wang, Dongshuo; Zhang, Luosheng; Bi, Yifeng; Zheng, Xinlei; Liu, Weibo; Bai, Guangjian; Wang, Zhenhua; Wan, Wei; Ma, Yong; Cai, Xiaopan; et al. (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is a primary malignant tumor of the bone characterized by poor prognosis due to chemotherapy resistance and high recurrence rates. DJ-1 (PARK7) is known as an oncogene and its abnormal expression is related to the poor prognosis of various types of malignant tumors. In this study, we found that DJ-1 was upregulated in OS and the level of DJ-1 was closely correlated with the prognosis of patients, and that DJ-1 could promote the proliferation, migration and chemotherapy-resistant of OS cells in vitro through regulating the activity of CDK4 rather through the oxidation mechanism or AKT pathway. The combination of DJ-1 and CDK4 promoted RB phosphorylation, leading to the dissociation of E2F1 into the nucleus to regulate the expression of cell cycle-related genes. The tumor xenograft mouse model demonstrated that knockout of DJ-1 suppresses tumor growth in vivo. All these findings indicate that DJ-1 can affect the occurrence and progression of OS by regulating the CDK/RB/E2F1axis, suggesting novel therapeutic opportunities for OS patients.